1935
DOI: 10.1128/jb.30.1.61-93.1935
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Freshwater Bacteria

Abstract: Pour se faire une ide'e suffisante sur les relations taxonomiques des bacte'ries, troupe devenues si important sous tant des rapports, il convient de ne pas se borner aux formes les plus habit uelles et d cause de cela les mieux connues; il faut diriger les recherches sur des bacteries particuli~res, capables de donner quelques aperfus nouveau sur la question de la morphologic du group en general."-ELIE METCHNIKOFF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1949
1949
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Thus, since the introduction of low nutrientmedia in Planctomycetes culture by Staley (Staley, 1973), a great technological accomplishments, several culture methods and media formulations for the isolation of planctomycetes were subsequently performed by others (Schlesner, 1994;Wiegand et al, 2020). Since most budding Planctomycetes lived in the attached state, the need of cell to attach to a solid support to ensure their reproduction (Henrici and Johnson, 1935) in the natural environment, the task would be difficult on ordinary solid agar used routinely in clinical microbiology laboratories for isolation. Hence, for the success of isolation, several enrichment techniques should be tried, and some enrichment experiments should take several months.…”
Section: Discussion and Perspectives Of Methods And Sources For The Ementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, since the introduction of low nutrientmedia in Planctomycetes culture by Staley (Staley, 1973), a great technological accomplishments, several culture methods and media formulations for the isolation of planctomycetes were subsequently performed by others (Schlesner, 1994;Wiegand et al, 2020). Since most budding Planctomycetes lived in the attached state, the need of cell to attach to a solid support to ensure their reproduction (Henrici and Johnson, 1935) in the natural environment, the task would be difficult on ordinary solid agar used routinely in clinical microbiology laboratories for isolation. Hence, for the success of isolation, several enrichment techniques should be tried, and some enrichment experiments should take several months.…”
Section: Discussion and Perspectives Of Methods And Sources For The Ementioning
confidence: 99%
“…Therefore, this organism was described as a fungus, and named Planctomyces bekefii Gimesi, 1924 (Gimesi, 1924;Jenkins and Staley, 2013;Dedysh et al, 2020a). In 1935, Henrici and Johnson found morphologically similar stalked, budding microorganisms in Lake Alexander (Minnesota, USA), but as these authors were unaware of Gimesi's previous report, they named this microorganism which they interpreted as bacteria Blastocaulis sphaerica (Henrici and Johnson, 1935). The authors also found spore-forming, drop-shaped, budding bacteria lacking a stalk, which they considered to be identical to Pasteuria ramosa Metchnikoff, 1888, a spore-forming bacterium that infects Daphnia species (Metchnikoff, 1888).…”
Section: Introductionmentioning
confidence: 99%
“…Examination of stained preparations under high magnification revealed that at least two different morphological types of attached bacteria were involved and that the organisms were affixed to the algal cell by some holdfast mechanism. The morphology of these organisms corresponds with the description given by Henrici and Johnson (1935) to periphytic bacteria growing on glass slides immersed in Lake Alexander, Minnesota, and named by them Caulobacter.…”
Section: Internal Factorsmentioning
confidence: 54%
“…It took a long time to create a relevant classification of this morphologically unusual group. For decades, stalked bacteria which reproduce by the separation of two cells morphologically and behaviourally different from each other, regardless of their habitat, were considered to be the members of the genus Caulobacter proposed by Henrici and Johnson in 1935 [5]. In 1992, Stahl et al .…”
Section: Full-textmentioning
confidence: 99%